Clinical and genetic analysis of a family with cerebrotendinous xanthomatosis - Guoliang, You; Zhaoxia, Wang; Lin, Zhang; Xuan, Chen; Xiaodong, Zhang; Xiaolian, Xing; Yangli, Su; Tianli, Zhang; Yanping, Zhu; Jiangping, Wang; Qing, Liu (Frontiers in Neurology, 2025)
ObjectiveThis study aims to analyze the clinical and genetic characteristics of cerebrotendinous xanthomatosis (CTX) in a Chinese family.MethodsClinical data, including medical history, neurologic and auxiliary examinations, imaging studies, and genetic profiles were collected from a Chinese CTX family at Taiyuan City Central Hospital. The proband underwent whole exome sequencing, which was confirmed via Sanger sequencing in two affected and five unaffected family members.ResultsTwo patients in the pedigree exhibited compound heterozygous missense variants in the CYP27A1 gene: c.379C > T, (pathogenic variants) and c.397 T > C, (a variant of uncertain clinical significance), both located in exon 2. A literature review revealed that c.1263 + 1G > A and C.379C > T are the most common variants in genetically diagnosed Chinese CTX patients, with exon 2 of the CYP27A1 gene.ConclusionThe compound heterozygous variants c.379C > T (p. Arg127Trp) and c.397 T > C (p. Trp133Arg) in the CYP27A1 gene are likely the cause of CTX in this pedigree. This finding expands our understanding of the genetic and clinical spectrum of CTX and provides significant insights for its diagnosis.